DETERMINATION OF THE AGE OF SAMALONA ISLAND CORAL REEF THROUGH C-14 ACTIVITY USING LSC METHOD (LIQUID SCINTILLATION COUNTIN - Wahyudin Wahyudin; Alfian Noor; Maming Maming (Marina Chimica Acta, 2019)
Analysis of 14C on samples of coral reefs on the Samalona Spermonde Islands vessel through 14C activity measurements using the LSC (Liquid Scintillation Counting) method was carried out. The preparation sample is carried out physically and chemically. Preparation of coral reefs with chemicals using a mixture of 1N NaOH and 30% H2O2 processed with a mixture of 1% HClO4 and 30% H2O2 and finally with 10% HCl to produce a clean sample by adding a weight of 5.36%. Carbonate separation was carried out using KOH as a carbosorb to produce K2CO3 solution. The total carbon is determined by the titration method which produces a total carbon of 0.9984 g. Measurement of 14C activity is done using LSC Hidex 300 SL. Specific activities of coral reef samples obtained were 15.06 ± 3.3613 DPM/gC. Age of coral samples on the island of Samalona in the Spermonde Islands was 130,343 ± 18.4 years.